Process oriented approaches in enterprise architecture for business-IT alignment - Malta, Pedro (2016)
Business-IT Alignment (BITA) has been an issue for researchers of Information and Systems Technology (IST) area for the last three or four decades. Many authors refer to BITA as a concern subject of IST managers, in what regards its achievement, but also its maintenance. Nevertheless, all approaches seem to be time and resources consumers, contrary to what would be desirable nowadays: achieve and maintain BITA quickly, efficiently and sustainably. Enterprise Architecture (EA) construction, as a way to BITA, especially when a Business Process Management (BPM) approach is used, a list of best practices should be obtained. Using Case Study methodology, with a data set content analysis, this paper intends to highlight benefits of using it, in process oriented approaches' to EA construction aiming BITA. Besides contribute to EA construction using process oriented methodologies, it is also important to consider the contribution to the Academy, with the scientific knowledge' increase in this area. And also the contribution to both involved consultancy companies, as well as to the organizations, in this case Municipalities, deserves attention: organization's processes are improved and real problems can be solved.